Aktivitas Sitotoksik Ekstrak Etanol Kulit Buah Pinang (Areca catechu) dan Daun Kayu Manis (Cinnamomum burmanni) - Wiwin Herdwiani; Soemardji AA; Elfahmi .; Tan MI; Nabila K; Anita K (Jurnal Farmasi Indonesia, 2018)
The areca plant (Areca cathecu) and cinnamon (Cinnamomum burmannii) haveanticancer properties. The aim of this research is to know the cytotoxic effect of Areca catechuof ethanol extract on T47D breast cancer cell culture and Cinnamomum burmannii leaves ofethanol extract on WiDr colon cancer cell culture.The obtained simplicia macerated to obtain ethanol extract of pinang peel and cinnamonleaves. The method used in testing cytotoxic activity was MTT (3- [4,5-dimethylthiazol-2yl] -2, 5-diphenyltetrazolium bromide) to obtain IC50 values.The results showed that ethanol extract of pinang peel and cinnamon leaf did not havecytotoxic effect on T47D culture with IC50 467,34 μg/mL and on WiDr culture with IC50 405,69μg/ml.